3D‐Printed Microfluidics: Formation of Polarized, Functional Artificial Cells from Compartmentalized Droplet Networks and Nanomaterials, Using One‐Step, Dual‐Material 3D‐Printed Microfluidics (Adv. Sci. 1/2020). Issue 1 (8th January 2020) - Li, Jin; Baxani, Divesh Kamal; Jamieson, William David; Xu, Wen; Rocha, Victoria Garcia; Barrow, David Anthony; Castell, Oliver Kieran
Abstract : In article number 1901719, David Anthony Barrow, Oliver Kieran Castell, and co‐workers create polarized artificial cells from compartmentalized droplet networks and nanomaterials, using multi‐material, 3D‐printed fluidics. Polarized patterning with magnetic microparticles bestow directional properties and motion in aqueous environments, with artificial cells exhibiting simple group‐level behaviors.